European stroke initiative recommendations for stroke management - update 2003 - Hacke, Werner; Kaste, Markku; Bogousslavsky, Julien; Brainin, Michael; Gugging, Maria; Chamorro, Angel; Lees, Kennedy; Leys, Didier; Kwiecinski, Hubert; Toni, Danilo; Olsen, Tom S.; Langhorne, Peter; et al. (Cerebrovascular diseases, 2003)
This article represents the update of 'European Stroke Initiative Recommendations for Stroke Management', first published in this Journal in 2000. The recommendations are endorsed by the 3 European societies which are represented in the European Stroke Initiative: the European Stroke Council, the European Neurological Society and the European Federation of Neurological Societies.